Cultura surda e língua brasileira de sinais (LIBRAS): pesquisa-ação sobre uma formação para profissionais da saúde pública - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The general objective of this research was to verify the contributions of a training course in LIBRAS and Deaf Culture for health professionals in order to provide more inclusive care for deaf patients. The theoretical framework addresses training and development for inclusive people management and care for deaf people in health services. An action research was carried out based on a LIBRAS and Deaf Culture course held by the Federal University of Pampa (UNIPAMPA) for health professionals from the Municipal Secretariat of Santana do Livramento-RS. It can be observed that care for deaf people in the municipality's public health services presents a precarious scenario, as there are no accessibility tools for the deaf community, in addition to there being no training policies and access to knowledge on this topic for employees. The majority had no knowledge of LIBRAS and more than 80% had never completed training in the area. The LIBRAS and Deaf Culture course was offered by UNIPAMPA for health professionals. During the course it was possible to notice the engagement of professionals with constant positive feedback. In this sense, the perception about the course and the potential to provide more inclusive care for deaf people was quite positive in both quantitative and qualitative responses. It was noticed that professionals feel more prepared, at least, to provide basic, more humane and qualified health care to a deaf person and encourage the city hall to continue offering this type of qualification.
Deaf culture and brazilian sign language (LIBRAS): action research on training for public health professionals
Keywords: Cultura surda; LIBRAS; Profissionais da saúde; Deaf culture; Health professionals; CNPQ::CIENCIAS SOCIAIS APLICADAS